A Fuzzy Controller for Compensation of Voltage Sag/Swell Problems Using Reduced Rating Dynamic Voltage Restorer - Rajesh Damaraju; S.V.N.L. Lalitha (Institute of Advanced Engineering and Science, 2015)
Non linear loads are highly effected by variations in voltages. Dynamic voltage restorer is one of the most popular compensating devices due to its low cost and better performance. Usage of Park’s transformation technique effectively reduces the rating of Dynamic voltage restorer. Application of fuzzy logic controller for getting the better result is proposed in this paper. The results are verified in Matlab/Simulink environment.